Pengembangan Modul IPA Terpadu Berbasis Discovery Learning Untuk Meningkatkan Motivasi Dan Hasil Belajar Peserta Didik Pada Materi Sistem Pernapasan Manusia - DWICAHYANI, ENDAH; SIALLAGAN, JOHNSON; VIRMAN, VIRMAN (Jurnal Ilmu Pendidikan Indonesia, 2020)
Research and development (R&D) aims to find out how to make integrated science modules based on discovery learning,feasibility of integrated science modules,increase motivation and learning outcomes of students using integrated sciencemodules,advantages and disadvantages of integrated science modules based on discovery learning in human respiratory system material Research results : 1) Development of integrated science modules based on discovery learning in human respiratory system material.2)Feasibility of integrated science learning based on discovery learning from the material validator the results of 91.30 % categories are very feasible, the results of the science teacher 93 % respone categories are very good, the response of limited-scale student is 88.78 %in very good categories.3) increased learning motivation of students by using integrated science modules based on discovery learning in human respiratory system material 81.83% very high categories,4)Improving student learning outcomes with an average the average pre test value of 39.06 was 70 in the post test and the n-Gain 0,51 moderate categories